When Performance Management Fails: Attitudes and Perceptions of Staff at a Higher Education Institution - Mntonintshi, Odwa; Mtembu, Vuyokazi (Journal of Economics and Behavioral Studies, 2019)
The implementation of Performance Management (PM) in an institution can come with barriers that affect its success rate. The aim of the study was to assess the perceptions and attitudes of staff towards the implementation of PM at a higher education institution. The research was undertaken at a higher education institution (HEI) in South Africa where employee performance suffered as a result of PM implementation challenges within the institution. The research study was exploratory and employed mixed methods, that is; quantitative and qualitative research methods. A survey questionnaire was administered to groups of university employees drawn through stratified random sampling. The strata groups were academics, administrators, and senior executive managers. Hundred questionnaires were distributed with eighty-three questionnaires returned. In qualitative research, a heterogeneous focus group interview was scheduled which involved twelve people. Results from the questionnaires indicated that respondents perceived PM process as lacking transparency, unaligned to employee rewards and development lacks objectivity from appraisers and poorly implemented due to lack of training for its users. Key themes that emerged from the focus group interviews revealed that the majority of participants perceived PM as a management punitive tool that is not developmental in orientation, a political tool that lacks objectivity and benefits only the employer. Furthermore, they articulated that it was not aligned with their rewards and development. It was therefore recommended that; proper design and implementation of the PM system is vital, fairness, training of all parties involved, moderation of results and providing effective feedback should be employed in PM, effective communication, transparency, consultation and shared benefits for all participants are key to ensuring a broadly supported PM within the institution.